CityFalcon: case study of a financial start-up - Bacha, Ruzbeh (Henry Stewart Talks, 2017)
Initiating a start-up, Ensuring sustainability, Building and motivating a team, Planning for the future, Importance of timing, Tips for operating a small business, Life as an entrepreneur